Proposed Knowledge Management Initiatives To Support Marketing Division Case Study At Pt Xyz - Aruan, Dewi Roybot Vetrauli br; Ghazali, Achmad (Ridwan Institute, 2024)
As an industry that requires the presence of branch offices in its marketing area, standardizing knowledge at the same level is a challenge in itself. Moreover, these differences can affect the company's performance, especially in sales. This study aims to see the level of readiness of knowledge management in the marketing division that is spread across various regions and to propose strategies related to knowledge management. The measurement was carried out using the Asian Productivity Organization (APO) KM assessment tool. The results of the study showed that there is an uneven level between one region and another. Therefore, the SECI process approach is recommended to specifically provide a way out for categories that receive low scores